Effective removal of chromium from wastewater with Zn doped Ni ferrite nanoparticles produced using co-precipitation method. (2021) - Shukrullah, Shazia; Azam, Muhammad; Naz, Muhammad Yasin; Toqeer, Irfan; Gungor, Afsin
Abstract: Zinc-nickel ferrite nanoparticles were synthesized using co-precipitation method and used to remove the chromium metal from the industrial wastewater. Before water treatment, the ferrite nanoparticles were characterized for their structure, morphology and size distribution using X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. Scherrer's formula was used to calculate the particle size from characteristic XRD peaks. The large surface area, controlled size and well-defined structure of the synthesized Ni-ZnFe2 O4 nanoparticles showed remarkable results for wastewater treatment. The characterized nanoparticles were distributed into the industrial wastewater under constant stirring for 20 min. The nanoparticles' suspension was subjected to UV–VIS spectrophotometry for the study of photo-catalytic behavior of Ni-ZnFe2 O4 nanoparticles. The effect of Ni-ZnFe2 O4 was investigated under visible light irradiation. Zn doping in Ni-ZnFe2 O4 showed remarkable effect on efficiency of Cr removal from wastewater.